2023
DOI: 10.1007/s40471-022-00317-5
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional Approaches to Minority Aging Research

Abstract: Purpose of Review Growing racial/ethnic diversity among America’s older adults necessitates additional research specifically focused on health and well-being among aging minoritized populations. Although Black and Latinx adults in the USA tend to face worse health outcomes as they age, substantial evidence points to unexpected health patterns (e.g., the race paradox in mental health, the Latino health paradox) that challenge our understanding of health and aging among these populations. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…There were no significant differences between the High Resource/Low Distress and Low Resource/Low Distress groups ( p = .91). There were no significant group differences on the memory composite (F = 1.68, p = .19, partial η 2 = 0.003). However, the groups significantly differed on subjective memory concerns (F = 143.14, p < .001, partial η 2 = 0.19).…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…There were no significant differences between the High Resource/Low Distress and Low Resource/Low Distress groups ( p = .91). There were no significant group differences on the memory composite (F = 1.68, p = .19, partial η 2 = 0.003). However, the groups significantly differed on subjective memory concerns (F = 143.14, p < .001, partial η 2 = 0.19).…”
Section: Resultsmentioning
confidence: 83%
“…There were no significant group differences on the memory composite (F = 1.68, p = .19, partial η 2 = 0.003). However, the groups significantly differed on subjective memory concerns (F = 143.14, p < .001, partial η 2 = 0.19). Pairwise comparisons revealed that the Low Resource/High Distress group had significantly greater memory concerns relative to the High Resource/Low Distress and Low Resource/Low Distress groups (ps < 0.001).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…This implies that distant relations may play an increasingly important role in understanding gender, racial/ethnic, and age disparities in mental health inequalities. A life course-intersectional lens (Brown, 2018;Liu & Lin, 2023;Thomas Tobin et al, 2023) is also needed as individuals' identities are closely intertwined with each other in producing and perpetuating social inequalities (Collins, 2019). Future research might extend the current research lines by investigating causal inferences, underlying mechanisms, and life course-intersectional disparities in greater depth.…”
Section: Discussionmentioning
confidence: 99%